Prevalence and Determinants of Burnout Among Palliative Care Clinicians in Saudi Arabia - Ghazwani, Eisa Yazeed (Frontiers in Public Health, 2022)
Background: Palliative care is in dire necessity than ever before due to ageing populations and the prevalence of cancer and other chronic diseases associated with ageing. Objective: To assess the prevalence and risk factors associated with burnout among palliative care clinicians in Saudi Arabia. Methods: A cross-sectional study conducted in 2018 covering all palliative care centers of Saudi Arabia and included 44 palliative care physicians (26 males and 18 females). The level of burnout was measured using Maslach Burnout Inventory’s (MBI) 22-point scale questionnaire which assesses emotional exhaustion, depersonalization, and reduced personal accomplishment, the three dimensions of burnout syndrome. Pearson correlation and binary logistic analysis were performed using SPSS to find out factors influencing burnout considering P value of <0.05 as significant. Results: Eight participants (18.2%) had experienced emotional exhaustion and 11 (25%) had experienced depersonalization & detachment, and reduced personal accomplishment, each. Job title and availability of some administrative departments, supporting health care staff, and pain relief medications have shown significant impact of level of burnout. However, the prevalence of the burnout dimensions did not differ significantly according to the palliative care physicians' other characteristics. Conclusions: This is amongst the first survey to assess the prevalence of burnout among palliative care physicians in Saudi Arabia. Although, some variables have shown significantly high level in the burnout domains, yet, the overall prevalence of burnout is low among palliative care physicians in Saudi Arabia. The availability of hospitals services such as administrative departments, supporting health care staff, and pain relief drugs have shown significant impact on burnout.